Initial testing (stage 1) of the notch inhibitor PF‐03084014, by the pediatric preclinical testing program. Issue 8 (24th March 2014) - Carol, Hernan; Maris, John M.; Kang, Min H.; Reynolds, C. Patrick; Kolb, E. Anders; Gorlick, Richard; Keir, Stephen T.; Wu, Jianrong; Kurmasheva, Raushan T.; Houghton, Peter J.; Smith, Malcolm A.; Lock, Richard B.
<x xml:space="preserve">Abstract</x> PF‐03084014, a γ‐secretase inhibitor, was tested against the PPTP in vitro cell line panel (1.0 nM to 10 μM) and against the in vivo xenograft panels (administered orally twice daily on Days 1–7 and 15–21). PF‐03084014 demonstrated limited in vitro activity, with no cell line achieving ≥50% inhibition. PF‐03084014 induced significant differences in EFS distribution in 14 of 35 (40%) solid tumor xenografts, and 1 of 9 ALL xenografts (which lacked a NOTCH1 mutation), but objective responses were not observed. PF‐03084014 demonstrated limited single agent activity in vitro and in vivo against the pediatric preclinical models studied. Pediatr Blood Cancer 2014; 61:1493–1496. © 2014 Wiley Periodicals, Inc.